Management of Stable COPD – a Clinical Review - Butterworth, Katrina (Journal of General Practice and Emergency Medicine of Nepal, 2011)
COPD is a progressive, systemic disease characterized by airflow limitation that is not fully reversible. There have been a number of recent advances in the management of COPD. The purpose of this review article is to raise awareness of these advances and encourage their implementation in the context of Nepal.